Green Investment: Incorporate Environment, Social, And Government Factors In Investment Decision - Pandu Adi Cakranegara; Filson Maratur Sidjabat (STIE PGRI Dewantara Jombang, 2021)
There are two types of investors, the first is the type of investor who focuses on return on investment and the second type is the investor who pays attention to Environmental, Social, and Governance (ESG) values in investing. This requires management to make adjustments to create a competitive advantage. One of the frameworks used to measure the competitive advantage of a company is the Porter framework. However, Porter's framework needs to be supplemented with ESG values to capture the value creation process in today's business environment. This research is applied research by applying the existing framework in the field. In this case, the framework used consists of two, namely the Porter framework and the LST integration framework. The ESG framework is implemented at the industrial level using industrial divisions based on industrial divisions in the Indonesia Stock Exchange. This study focused on the raw material production sector, namely agriculture, and mining. This study showed that ESG factors affected the competitive advantage of companies and industries. If a company in an industry ignores the value of ESG, the company will experience a decrease in competitiveness. Meanwhile, if the industry does not pay attention to the ESG factor, the industry will experience a decline compared to other industries that pay attention to the ESG factor.